Revitalsasi Moral Dalam Pendidikan : Telaah Konsep Pendidikan Moral Ibnu Maskuya - Handriawan, Dony (Fikroh: (Jurnal Studi Islam), 2023)
فيها عدم ادخال نتاءج الأخلاق الإسلامية في كل عماليتها. عدة المشكلات التربوية Berbagai problem yang mendera dunia pendidikan saat ini tidak dapat dielakkan lagi adalah salah satu imbas dari terabaikannya aspek moral dalam praktek pendidikan yang berlangsung saat ini. Various problems plaguing the education sector today, suspected to be one consequence of eroding, even the loss of a spirit of true morality in education. No doubt, when it is no longer a moral foundation and a principal goal of education, then it is certainly going long tails on the emergence of bigger problems, not only will befall in education its self, but will spread to other dimensions, such as social and politics. Moral revitalization in education is the key word and long-term solutions. Moral education is not only to be one of the functions of education, but more than that morality should be the ultimate goal convening of an education. Because the intellect is not based on morality, has been ascertained only will produce successive generations of "disability", which is only going to ruin the social life of the nation. Corruptor is a concrete manifestation of the erosion of the morality of intellectual, our educational products. Than this paper attempts to unravel the true concept of moral education has been touted 11 centuries ago by a leader, named Ibn Maskuya.